How cyber insurance can still leave you vulnerable to risks. Issue 2 (February 2020) - Stephens, Sarah
Abstract : Welcome to the 2020s, where every sector and company, regardless of size, is heavily reliant on technology to facilitate its operations, communication and dealings with its supply chain. In this digital climate, cyber attacks pose an increasingly significant business risk, which has resulted in cyber security steadily climbing up the C-suite's priorities agenda. Companies are still struggling to grasp the extent of their cyber risk exposure, and this creates an unnecessary roadblock for every organisation that could benefit from cyber risk transfer. It would be reasonable to assume that companies are shifting their risk perception from the physical to the digital and in turn adjusting the way they insure against risk. However, firms remain chronically underinsured against cyber risk. Senior management and board-level leadership must embrace cyber risk as an issue so the conversation can be driven top down and bottom up, says Sarah Stephens of Marsh JLT Specialty.